THE EFFORTS TO IMPROVE LEARNING OUTCOMES ON LINEAR EQUATION SYSTEMS THREE VARIABLES BY USING POWER POINT MEDIA - Niki Ari Afgani ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
In Learning System of  Three Variable Linear Equation System Mathematics class X of  Integrated High School Ar-Risalah still many under KKM (KKM 60) especially in solving the problems. Therefore, it is necessary an effort to improve the learning outcomes of  Mathematics is through the media power point. This study aims to determine the improvement of  learning outcomes of students class X IPA of Integrated High School Ar-Risalah academic of year 2017/2018  in the problems solving on the subject of SPLTV through power point media. The subjects of the study were the students class X IPA of Integrated high school Ar-Risalah of  22 students, a Mathematics teacher and 4 observers. Data collected included student learning outcomes, teacher observation results, student observation results. This research is a Classroom Action Research conducted in three cycles. Each cycle includes are 4 (four) stages of planning, action implementation, observation (observation) and reflection. The average value of test results cycle II, 53.18 increased by 30.49 compared to the average value of the results of the test cycle I, namely 22.69. And the average value of the third cycle test results that is 70.80 increased by 17.62 compared to the average value of the second cycle test results. Based on the performance indicator, in conclusion, that the result of  the study, the students of Integrated High School Ar-Risalah on SPLTV can be improved through power point media.